Proceedings of the 5th ACM Workshop on Embedded Systems for Energy-Efficient Buildings 2013
DOI: 10.1145/2528282.2528293
|View full text |Cite
|
Sign up to set email alerts
|

It's Different

Abstract: Residential buildings contribute significantly to the overall energy usage across the world. Real deployments, and collected data thereof, play a critical role in providing insights into home energy consumption and occupant behavior. Existing datasets from real residential deployments are all from the developed countries. Developing countries, such as India, present unique opportunities to evaluate the scalability of existing research in diverse settings. Building upon more than a year of experience in sensor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Three different publicly available databases were used, namely the ECO [50], the REDD [51], and the iAWE [52] database. The ECO and REDD databases consist of different datasets with each of them containing power consumption recordings from different houses, while iAWE database consists of recordings from one house.…”
Section: Databasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Three different publicly available databases were used, namely the ECO [50], the REDD [51], and the iAWE [52] database. The ECO and REDD databases consist of different datasets with each of them containing power consumption recordings from different houses, while iAWE database consists of recordings from one house.…”
Section: Databasesmentioning
confidence: 99%
“…The utilized datasets are available online and free to download under common creative licence (ECO [50] (10.5905/ethz-1007-35), REDD (http:// redd.csail.mit.edu/) [51] and iAWE [52] (https://iawe.github.io/)).…”
Section: Fundingmentioning
confidence: 99%
“…The Almanac of Minutely Power dataset (AMPds) [15] was also released that year containing both aggregate and sub-metered power data from a single household. Subsequently, the Indian data for Ambient Water and Electricity Sensing (iAWE) [16] was released, which contains both aggregate and sub-metered power data from a single house. Most recently, the UK Domestic Appliance-Level Electricity data set [17] (UK-DALE) was released which contains data from four households using both aggregate meters and individual appliance sub-meters.…”
Section: Public Data Setsmentioning
confidence: 99%
“…Batra et al showed voltage fluctuates from 180-250 V in the iAWE data set collected 5 http://nilmtk.github.io/nilmtk/stats.html in India [16], while the voltage in the Smart* data set varies across the range 118-123 V. Hart suggested to account for these voltage fluctuations as they can significantly impact power draw [1]. Therefore, NILMTK provides a voltage normalisation function based on Hart's equation:…”
Section: Preprocessing Of Data Setsmentioning
confidence: 99%
“…In 2011, researchers at MIT released the first public dataset for energy disaggregation research [10]. Since then, over ten more datasets have been released [1]- [3], [9], [12], [14] and, in March 2014, a project called Wiki Energy 1 launched to share datasets online. These datasets have been well received but, because each dataset uses a different file format, it is time consuming to import multiple datasets.…”
Section: Introductionmentioning
confidence: 99%